2002
DOI: 10.1016/s0014-5793(02)03513-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the amino terminal subunit of the glycoprotein of Borna disease virus

Abstract: The only surface membrane glycoprotein of Borna disease virus (BDV) is synthesized as a polypeptide with a molecular mass of 57 kDa and N-glycosylated to a precursor glycoprotein (GP) of about 94 kDa. It is processed by the cellular protease furin into the C-terminal membrane-anchored subunit GP-C, also known as gp43, and a presumptive N-terminal subunit GP-N, that is highly glycosylated and has a molecular mass of about 51 kDa. However, up to now the latter remained undetected in BDV-infected material. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…As shown in Fig. 1, the molecular mass of GP1 was consistent with that of the wild-type GP1, as described in previous reports [8,12], and all constructs were efficiently expressed in 293T cells.To verify that GP1 binds to BDV-permissive Vero cells but not to non-permissive Chinese hamster ovary (CHO) cells [2], cells were first incubated with 1.5 µg/ml of FLAGtagged GP1, and the binding of this to cells was then detected using an anti-FLAG M2 antibody. Flow cytometric analysis indicated that GP1 bound to Vero but not to CHO cells (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 1, the molecular mass of GP1 was consistent with that of the wild-type GP1, as described in previous reports [8,12], and all constructs were efficiently expressed in 293T cells.To verify that GP1 binds to BDV-permissive Vero cells but not to non-permissive Chinese hamster ovary (CHO) cells [2], cells were first incubated with 1.5 µg/ml of FLAGtagged GP1, and the binding of this to cells was then detected using an anti-FLAG M2 antibody. Flow cytometric analysis indicated that GP1 bound to Vero but not to CHO cells (Fig.…”
supporting
confidence: 86%
“…Cellular furin-like proteases cleave the G protein into the ectodomain subunit GP1 and the transmembrane subunit GP2 [13]. GP1 (51-60 kDa) is highly glycosylated and sufficient to mediate viral entry [8,11]. GP2 (43 kDa) has a putative fusion domain at the N-terminus that is involved in the pH-dependent fusion event [6].…”
mentioning
confidence: 99%
“…7B). This protein likely corresponds to a partially glycosylated GPC, suggesting that furin-mediated maturation of BDV G may be involved in the complete glycosylation of BDV G. We have generated a novel Ab (Ab-GP1 N ) capable of detecting GP1 efficiently without the need of endoglycosidase treatments (16), which allowed us to examine the levels of GP1 in BDVinfected cells and virions. The use of Ab-GP1 N , together with the previously described Ab-G (11), revealed that all three BDV G species, GPC, GP1, and GP2, are incorporated into virions.…”
Section: Discussionmentioning
confidence: 99%
“…GPC is posttranslationally cleaved by the cellular protease furin into GP1 (GP N ) and GP2 (GP C ), which correspond to the N-and C-terminal regions, respectively, of GPC (9,27). GPC and GP2 are readily detected in both infected cells and cell-free virions (9,10), whereas antibody (Ab) detection of GP1 has been complicated by its high content of N-glycans that shield antigenic sites (16).…”
mentioning
confidence: 99%
“…The C-terminus product (GP2) is readily detected in virally infected cells and migrates with an M r of 43,000. In contrast, detection of the predicted N-terminal product (GP1) of G has been difficult due to its high content of N glycans, which shield antigenic sites recognized by antibodies (18). GPC accumulates in the endoplasmic reticulum and perinuclear region, but it is typically not detected on the plasma membrane, whereas GP2 accumulates at the cell surface (13).…”
mentioning
confidence: 99%